Co-producing rapid research: Strengths and challenges from a lived experience perspective - Machin, Karen; Shah, Prisha; Nicholls, Vicky; Jeynes, Tamar; TK,; Trevillion, Kylee; Vera San Juan, Norha (Frontiers in Sociology, 2023)
The Lived Experience Researchers (LERs) of the Mental Health Policy Research Unit (MHPRU) reflect on the experience of conducting rapid co-produced research, particularly during the first year of the COVID-19 pandemic. Throughout this perspective article, we introduce requirements for co-production applying the 4Pi Framework, reflect on specific characteristics of co-production in rapid research, discuss strengths and challenges for involvement of LERs in rapid research, and lastly provide recommendations to achieve meaningful involvement. Incorporating meaningful co-production is an augmentation to any research project, with several benefits to the research, to the team, and to individual researchers. Particularly in the case of rapid research, that aims for efficient translation of knowledge into practice, involvement of experts by experience will be key. The work conducted by the MHPRU LERs presented in this paper demonstrates the viability, value, and potential of this way of working.